Citizen participation: models and methods - Callahan, Kathe (2007)
The belief that individuals should be given a voice in their governance appeals to our democratic ideals and in fact has long been identified internationally as one of the unique aspects of the United States. While there appears to be universal agreement that the involvement of citizens in the decision making process of government is a good idea, there is little agreement as to the best way to achieve meaningful involvement. There are many ways to consult with the public and get a sense of what they see as problems and opportunities; it is quite another thing to actively engage citizens in the decision-making process. This paper explores the challenges and dilemmas associated with direct citizen participation, reflects on the various models of citizen-government interactions and makes recommendations for moving beyond conventional participation. While the benefits of including citizens in the deliberative process are widely recognized, citizen participation is not routinely sought in the decision making process. - Reproduced.
Keywords: Workers participation